2018
DOI: 10.1186/s12890-018-0754-x
|View full text |Cite
|
Sign up to set email alerts
|

National survey: current prevalence and characteristics of home mechanical ventilation in Hungary

Abstract: BackgroundHome mechanical ventilation is an established treatment for chronic respiratory failure resulting in improved survival and quality of life. Technological advancement, evolving health care reimbursement systems and newly implemented national guidelines result in increased utilization worldwide. Prevalence shows great geographical variations and data on East-Central European practice has been scarce to date. The aim of the current study was to evaluate prevalence and characteristics of home mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…When looking at other factors potentially influencing HRQL change, we found that HRQL increase was the greatest among patients with lower initial HRQL scores, patients initiated with long term mechanical ventilation in an acute setting, and patients needing supplemental O 2 therapy, implying that a lot of patients included in the current study might have received home mechanical ventilation relatively late in their course of disease progression. This is corroborated by the study previously published by our group that describes the current characteristics and prevalence of HMV in Hungary [ 37 ], which found that prevalence of home mechanical ventilation is lower than that found in other internationally published data, because many ventilator-dependent patients might not receive therapy in time. This finding is especially important, since there is still no clear data to help us differentiate between long term therapeutic home mechanical ventilation and palliative care with ventilation.…”
Section: Discussionsupporting
confidence: 84%
“…When looking at other factors potentially influencing HRQL change, we found that HRQL increase was the greatest among patients with lower initial HRQL scores, patients initiated with long term mechanical ventilation in an acute setting, and patients needing supplemental O 2 therapy, implying that a lot of patients included in the current study might have received home mechanical ventilation relatively late in their course of disease progression. This is corroborated by the study previously published by our group that describes the current characteristics and prevalence of HMV in Hungary [ 37 ], which found that prevalence of home mechanical ventilation is lower than that found in other internationally published data, because many ventilator-dependent patients might not receive therapy in time. This finding is especially important, since there is still no clear data to help us differentiate between long term therapeutic home mechanical ventilation and palliative care with ventilation.…”
Section: Discussionsupporting
confidence: 84%
“…The most common diagnosis for home mechanical ventilation in our study population was OHS/OSAS, which is an increasingly common indication for HMV in recent years [18]. It has been reported before that the majority of Hungary's HMV population has begun treatment in the last 5 years with OHS being the most frequent indication, attributing to the composition of our cohort [2]. Our results of the SRI Questionnaire in this patient group indicate that OHS/ OSAS causes similair quality of life limitation to other chronic respiratory failure conditions, with SRI-PF and -WB scales being the most affected aspects.…”
Section: Discussionmentioning
confidence: 63%
“…Prevalence has been growing worldwide with the aid of evolving technical possibilities, telemedicine and improved national guidelines. The prevalence in Hungary has been reported to be lower than in leading countries worldwide, although improved reimbursement has vitalized the field and has resulted in increased awareness and evolving care for chronic respiratory failure patients [2]. Projects to establish a national guideline and registry for patients treated with home mechanical ventilation are currently under way in the country, hence the need to develop a quality of life survey for this specific group of patients that can be administered for adequate evaluation and follow up.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, and on the basis of available studies, the current prevalence of HMV is expected to be higher than described in the Eurovent study, even in countries where this practice has not been as widespread in the last decade. In addition, the organization lacks comparisons with new publications [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of diagnoses for which it is appropriate to use home mechanical ventilation. Amyotrophic lateral sclerosis was used as it is the most common diagnosis from the neuromuscular group of diseases [ 13 , 14 , 15 ]. The aim of this study is to perform a cost–utility analysis (CUA) of home mechanical ventilation in adult patients with amyotrophic lateral sclerosis in comparison with mechanical ventilation in a healthcare facility from the perspective of a healthcare payer in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%